2018
DOI: 10.29100/jipi.v3i1.652
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Pembelajaran Bentuk Molekul Kimia Menggunakan Augmented Reality Berbasis Android

Abstract: Seiring dengan perkembangan pada dunia pendidikan yaitu muncul berbagai macam media pembelajaran baru Salah satu teknologi yang cukup menarik saat ini yang dapat dikembangkan pada Android adalah Augmented Reality (AR). AR dapat memberikan informasi yang dapat lebih mudah dipahami oleh pengguna. Karena kelebihan yang dimiliki, AR dapat dimanfaatkan untuk membuat aplikasi pembelajaran yang dapat mendukung proses belajar mengajar. Salah satu pelajaran yang dapat memanfaatkan teknologi ini adalah pelajaran kimia m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 8 publications
0
15
0
11
Order By: Relevance
“…3) The learning process can be done anywhere and anytime. By using AR technology, students can see and manipulate geometric concepts related to space, so that students feel interested in learning and can understand the concept of space well [22]. In addition, by using AR technology as a learning medium, students can learn and manipulate the objects presented in AR so that students can study regularly at home or anywhere until students are able to construct their knowledge [9].…”
Section: Augmented Reality In Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…3) The learning process can be done anywhere and anytime. By using AR technology, students can see and manipulate geometric concepts related to space, so that students feel interested in learning and can understand the concept of space well [22]. In addition, by using AR technology as a learning medium, students can learn and manipulate the objects presented in AR so that students can study regularly at home or anywhere until students are able to construct their knowledge [9].…”
Section: Augmented Reality In Learningmentioning
confidence: 99%
“…In addition, by using AR technology as a learning medium, students can learn and manipulate the objects presented in AR so that students can study regularly at home or anywhere until students are able to construct their knowledge [9]. In addition, Augmented Reality is able to provide a picture or information that can be more easily understood, therefore Augmented Reality can be used for learning applications [22]. Based on these thoughts, the use of AR-based mathematics learning media in the learning process will be able to provide a good influence on students in constructing their knowledge related to learning materials for Geometry in elementary schools.…”
Section: Augmented Reality In Learningmentioning
confidence: 99%
“…Kemampuan peserta didik dalam menyelesaikan permasalahan kimia akan meningkat seiring dengan bertambahnya pemahaman pada level submikroskopik [7] . Pemahaman bentuk molekul pada tingkat submikroskopik dapat dibantu dengan menggunakan alat bantu belajar atau media yang dapat memberikan gambaran kongkrit kepada peserta didik sehingga belajar bentuk molekul bukan hanya sekedar menghafal tetapi lebih dari memahami konsep bentuk molekul secara menyeluruh [8] . Untuk mengatasi permasalahan tersebut, dibutuhkan media pembelajaran yang dapat menarik minat peserta didik yaitu pemodelan.…”
Section: Pendahuluanunclassified
“…Research by Hafidha & Sudarmilah [15], namely the development of AR on the material Periodic System Elements yield based applications android good look, operational, and material and test results indicate that over 80% of respondents said AR application on the material Periodic System Elements excellent. By Supriono [16] showed that the application can run well, the test results portability of 96.7%, can be used on all smartphones except the resolution widened as tabs, and there are features of the periodic table that can be used directly in applications. The purpose of this development to produce a product of teaching materials based on the AR-assisted 5E LC material reaction rate valid and feasible to be implemented in learning.…”
Section: Introductionmentioning
confidence: 99%